0D/3D NiCo2O4/defected UiO-66 catalysts for enhanced degradation of tetracycline in peroxymonosulfate/simulated sunlight systems: Degradation mechanisms and pathways. (July 2022) - Wang, Yuhan; Liu, Chang; Wang, Chao; Hu, Qing; Ding, Longzhen
Abstract: Developing synergistic systems and taking environmental risks into account are two necessary aspects of being considered to remove persistent organic pollutants efficiently. Thus, a combined catalytic system uniting the Fenton-like process and simulated solar-light photocatalysis has been constructed. Moreover, a series of NiCo2 O4 /HP-UiO-66 catalysts (yNiCo-DUx) were also fabricated to improve tetracycline (TC) removal efficiency. The NiCo2 O4 nanoparticles (NPs) and hierarchically porous metal-organic frameworks (HP-MOFs) were synthesised using one-step calcination. The Z-scheme structure of the catalysts was confirmed by ESR, XPS, DRS, time-resolved PL (TR-PL) spectra and the quenching experiments. The NiCo2 O4 nanoparticles could be embedded and fixed into the defects of the MOF structure, and the leaching of toxic metals was also significantly suppressed. In the optimal reaction condition with 15NiCo-DU50, sunlight, and peroxymonosulfate (PMS), the total removal efficiency of TC could reach 98.5% within 8 min of irradiation, and the highest % RSE could reach 11.2%. Moreover, the corresponding reaction rate was 28.7, 3.6 and 1.3–10.2 times higher than photocatalysis, Fenton-like processes and other catalysts. Furthermore, the possible degradation mechanism, generation of reactive species and PMS excitation pathways were also investigated in depth. The present study sheds light on the fabrication of HP-MOFs based catalysts and the combination of various methods to eliminate organic pollutants. Graphical abstract: Image 1 Highlights: Hierarchically porous MOFs were fabricated using selective linker thermolysis. Defected MOF-coated NiCo2 O4 catalysts were prepared by one-step calcination. The highest % RSE value could reach 11.2% in the constructed systems. Photocatalytic and non-photocatalytic processes were distinguished. Radical and non-radical pathways were also elucidated.